Red shifted spectral dependence of the SERS enhancement in a random array of gold nanoparticles covered with a silica shell: extinction versus scattering. (23rd October 2015) - D'Andrea, C; Irrera, A; Fazio, B; Foti, A; Messina, E; Maragò, O M; Kessentini, S; Artoni, P; David, C; Gucciardi, P G
Abstract: We report on the spectral dependence of the SERS amplification in randomly distributed gold nanoparticle arrays grown by electron beam evaporation, covered with a thin shell of SiO2 . Experiments carried out with six different laser lines highlight a remarkable red-shift between the optimal excitation wavelength (785 nm) and the localized plasmon resonance peak (560 nm) measured by extinction spectra. The different enhancement undergone by the vibrational peaks of the probe molecule is studied as a function of the excitation energy. The origin of such a shift is discussed in terms of the scattering efficiency of the gold nanoparticles.